A clinical case of transthyretin amyloidosis with manifestations of seronegative arthritis - V. A. Mareeva; A. A. Klimenko; E. R. Moskalets; P. A. Glazunov; N. A. Shostak; E. V. Zhilyaev (Klinicist)
Introduction. A clinical case of an 80-year-old patient with clinical and instrumental manifestations of amyloidosis caused by the deposition of non-mutant (“wild type”) transthyretin (Amyloidosis “wild type” TransThyRetin, ATTRwt) is described. A special feature of this case was the diagnosis of amyloidosis at the same time as the identification of symmetrical polyarthritis.Aim. To present an example of successful diagnosis and timely treatment of ATTRwt amyloidosis.Materials and methods. Male patient (80 years old) consulted a rheumatologist in an outpatient clinic with complaints of weakness and pain in the muscles of the upper and lower extremities, swelling and soreness of both wrist joints; with manifestations of multiple tunnel syndromes (ulnar canal, Guyon canals, bilateral carpal tunnel syndrome). In addition, the patient had a heart involvement which appeared as left ventricle hypertrophy, paroxysmal form of atrial fibrillation, chronic heart failure with preserved ejection fraction, intraventricular conduction defect and low QRS voltage. Due to the presence of cardiac manifestations along with neuropathy, transthyretinic amyloidosis was suspected.Results. Polyneuropathy was confirmed by the results of electroneuromyography. AL-amyloidosis (immunoglobulin Light chain Amyloidosis) is excluded due to the absence of monoclonal proteins in the blood. The diagnosis was confirmed by the results of scintigraphy with with labeled technetium-99m pyrophosphate. Intensive accumulation of radiopharmaceutical was detected in the myocardium of the left ventricle. The study also confirmed the presence of polyarthritis, manifested by increased accumulation, in the area of the I metatarsophalangeal joint on the left, both wrist, shoulder and knee joints. The hereditary nature of ATTR amyloidosis was excluded by the results of genetic analysis, which did not reveal mutations in the transthyretin gene. The singularity of this case was in development of a symmetrical polyarthritis during amyloidosis manifestation. Pathogenetic therapy with tafamidis was initiated. Arthritis regressed after starting treatment with methotrexate.Conclusion. Transthyretin amyloidosis is a chronic progressive life-threatening disease caused by the formation and deposition of transthyretin-derived amyloid fibrils. The variety of amyloid tropicity to various organs and tissues leads to it phenotypic heterogeneity, which makes it difficult to make a diagnosis on early stages. However, the detection of «red flags» symptoms signaling the presence of transthyretin amyloidosis can shorten the time before initiation of targeted treatment, contributing to the improvement of the patient’s quality of life.